Promotion of Manufactured Exports in Sri Lanka : the role of the government - Fernando, Shanthikumar; University of Colombo. Economics Department (Colombo : Department of Economics, University of Colombo, 2016)
"This study is concerned with the role of the government in promoting manufactured exports in developing countries with specific reference to Sri Lanka"--Back cover."
Originally presented as author's thesis (doctoral)--University of Colombo, 2012.
Includes bibliographical references (pages 199-206).
Keywords: Foreign trade promotion -- Sri Lanka; Manufacturing industries -- Government policy -- Sri Lanka; Exports -- Sri Lanka; Free trade -- Sri Lanka; Sri Lanka -- Commercial policy